2020
DOI: 10.1097/j.pbj.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut microbiota in metabolic syndrome: a review of recent evidence

Abstract: The metabolic syndrome is a complex entity comprised of multiple cardiovascular risk factors grouped in a single individual, contributing to an increased rate of cardiovascular events which goes beyond what would be expected given the impact of each individual risk factor. It is a multifactorial condition whose complete pathogenesis is not yet fully understood. Several studies have shown that not only the intestinal microbiota and dysbiosis may play a role in its pathogenesis, but also that modulating said mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Accumulating evidence has recognized MetS to be a systemic proinflammatory state with gut flora dysbiosis and adipose inflammation as putative pathogenic mechanisms. A series of studies showed that chronic high-fat diets (HFDs) could alter gut microbiota composition and cause defects of the intestinal barrier that facilitate enterotoxin entry into systemic circulation ( Cani et al., 2007 ; Greenhill, 2015 ; Alveirinho et al., 2020 ). Meanwhile, rapid hypertrophy of adipocytes results in tissue hypoxia and secretion of adipokines (such as IL-6 and TNF-α), which recruit macrophages to secrete proinflammatory factors, exacerbating systemic inflammation and further contributing to insulin resistance ( Lumeng et al, 2007 ; Winer et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has recognized MetS to be a systemic proinflammatory state with gut flora dysbiosis and adipose inflammation as putative pathogenic mechanisms. A series of studies showed that chronic high-fat diets (HFDs) could alter gut microbiota composition and cause defects of the intestinal barrier that facilitate enterotoxin entry into systemic circulation ( Cani et al., 2007 ; Greenhill, 2015 ; Alveirinho et al., 2020 ). Meanwhile, rapid hypertrophy of adipocytes results in tissue hypoxia and secretion of adipokines (such as IL-6 and TNF-α), which recruit macrophages to secrete proinflammatory factors, exacerbating systemic inflammation and further contributing to insulin resistance ( Lumeng et al, 2007 ; Winer et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%